Peran Orang Tua Dalam Miningkatkan Motivasi Belajar Peserta Didik di Sd Negeri Saribi - Selfia S. Rumbewas; Beatus M. Laka; Naftali Meokbun (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2018)
The purpose of this study is to determine the role of parents in improving motivation learners in elementary school Saribi Orkeri District Biak Numfor District. The type of approach taken in this research is to use a qualitative approach. Qualitative research that will be conducted directly with a long time stages and directly included in the scope of the environment, but qualitative research is generally analyzed by inductive approach, especially at the time of the initial study. In this study the authors use descriptive research type that aims to describe the real things related to real conditions in the field. The tools used in this study are questionnaires, interview guides, and documentation. After the data is collected then, the authors analyzed by using descriptive analysis. The results of this study indicate that parents are instrumental in generating learning motivation learners. This was conveyed by one of the children who stated